Critical heat flux in a closed two-phase thermosyphon; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 196 : Actual Problems of Thermal Physics and Physical Hydrodynamics - Ponomarev K. O. Konstantin Olegovich (2019, 2019)
Title screen